Exploring the Potential of Eltrombopag: Room for More? - Tarantini, Francesco; Cumbo, Cosimo; Anelli, Luisa; Zagaria, Antonella; Conserva, Maria Rosa; Redavid, Immacolata; Specchia, Giorgina; Musto, Pellegrino; Albano, Francesco (Frontiers in Pharmacology, 2022)
Since its introduction in clinical practice, eltrombopag (ELT) has demonstrated efficacy in heterogeneous clinical contexts, encompassing both benign and malignant diseases, thus leading researchers to make a more in-depth study of its mechanism of action. As a result, a growing body of evidence demonstrates that ELT displays many effects ranging from native thrombopoietin agonism to immunomodulation, anti-inflammatory, and metabolic properties. These features collectively explain ELT effectiveness in a broad spectrum of indications; moreover, they suggest that ELT could be effective in different, challenging clinical scenarios. We reviewed the extended ELT mechanism of action in various diseases, with the aim of further exploring its full potential and hypothesize new, fascinating indications.